Employee Stock Ownership Program (ESOP), Intellectual Capital dan Nilai Perusahaan : Efek Mediasi dari Kinerja Keuangan (Studi pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2019) - Sulistyaningsih; Hidayatul Khusnah (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
The purpose of this research to test the ESOP, Intellectual Capital and Firm Value : The mediation effect of financial performance. Independent variables in this study are ESOP and Intellectual Capital. The dependent variables in this study are the firm value and financial performance as mediation variables. This study used secondary data, namely data obtained from annual financial statement and consolidated financial statement of non-financial companies registered with IDX during the period 2014-2019. There are 10 companies sampled in this study. This study used purposive sampling method and analyzed the data using WarpPLS 6.0 application. Analysis shows that ESOP has a negative and significant effect on financial performance. IC (VACA, VAHU and STVA) shows only VACA and STVA have a positive and significant effect, while VAHU has no effect on financial performance. Financial performance using ROA indicators will have a positive and significant effect on the firm value from the Tobins’Q. ESOP indicator has a no impact on the firm value. VACA, VAHU and STVA have a positive and significant effect on the firm value. Financial performance cannot mediate the influence of ESOP and VAHU on the firm value. However, financial performance can mediate the influence between VACA and STVA on the firm value.